(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Agriculture is the practice of cultivating plants & live stocks. Agriculture is the key for the growth in rising sedentary human living whereas the farming of the domesticated species creates the food surplus which enabled the people for living in cities. Agriculture is significant not only in the supply of food but also in the provision of raw materials to other industries like sugar, tobacco, jute, textiles & vegetable oil. Agriculture is the way of life and also the occupation of the people. Most of the cultures and customs revolve around agriculture. Agriculture is the method of farming and the cultivation of animals, plants, medicinal plants, fungi, and other products that are utilized for enhancing human life. Agricultural science is the study of agriculture. This article discusses current advances in the realm of agriculture as well as their many ramifications. India will need many types of agricultural and land-based solutions in the future. India needs to shift from basic farming towards much efficient, sustainable & productive farming methods for increasing the yield and fulfilling the demands of those engaging in Agriculture.